Factors Predicting Postoperative Malnutrition in Trauma Patients - thawongpia, nattika; Chanruangvanich, Wallada; Thosingha, Orapan; Prichayudh, Supparerk (Journal of Thailand Nursing and Midwifery Council, 2021)
Objective: To study the predictive powers of injury severity, energy intake during 72 hours after surgery, and fever during 72 hours after surgery towards malnutrition in postoperative trauma patients Design: Predictive correlation research Methodology: The subjects were 137 trauma patients admitted to the surgery ward of a tertiary hospital. The data collection instruments consisted of: (i) a general information record form; (ii) a form for recording injury severity, energy intake and need, and temperature during 72 hours after surgery; (iii) a ﬂuid intake and discharge record form; and (iv) a malnutrition assessment form. The data were analysed using the binary logistic regression analysis, with the signifcance level set at 0.05. Results: The majority of the subjects were male (70.10%). Symptoms of malnutrition became apparent in over three-thirds (76.60%) of the subjects on the eighth day after being admitted for treatment, with 78.80% of these subjects recording ≥ 9 injury severity level. All the subjects’ average energy intake was 784.2 Kcal, lower than half of the estimated energy need average of 1,704.36 Kcal, whilst fever was found in 37.20% of the subjects. The analysis revealed that injury severity, energy intake during 72 hours after surgery, and fever were capable of predicting malnutrition in trauma patients by 31%, at a statistically signifcant level of .01 (Nagelkerke R2 = 0.31, p < 0.01). Recommendations: Nurses are advised to pay close attention to trauma patients’ nutrition, especially those with the injury severity level of ≥ 9, to ensure the patients receive more than 50% of the recommended average individual energy need.